2020
DOI: 10.1021/acs.inorgchem.9b03466
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Metal–Organic Framework Derived from Sacrificial Cobalt Nanowire Template Interconnected with Nickel Foam Supported Selenite Network as an Integrated 3D Electrode for Overall Water Splitting

Abstract: The development of bifunctional, highly active electrocatalysts for an overall water splitting reaction remains a major challenge. Here, the sacrificial template-assisted transformation of cobalt hydroxide nanowire (Co(OH) 2 NW) into a metal−organic framework network (MOF) is conceived as a porous structure that provides extremely active and durable electrochemical energy conversion characteristics. After this, the 1D MOF modified Co NWs can be further transformed into a hybrid structure (MOF CoSeO 3 NWs) by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 59 publications
6
32
0
Order By: Relevance
“…For comparison, MOF Co, MOF Cu, and MOF CoCu nanocubes were also performed. As can be seen in Figure 3A, the XRD pattern of MOF Co (a) and MOF Cu (b) is exactly matched with our previous report [34, 35]. Figure 3A (c) shows the XRD pattern of MOF CoCu nanocubes with several peaks at 2θ of about 7.16, 10.2, 12.6, 14.4, 16.3, 17.9, 22.0, 24.5, 26.6, 29.6, 31.2, and 32.3° associated with (011), (022), (112), (022), (013), (222), (114), (233), (134), (044), (244), and (235) diffraction planes of MOF Co [35].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For comparison, MOF Co, MOF Cu, and MOF CoCu nanocubes were also performed. As can be seen in Figure 3A, the XRD pattern of MOF Co (a) and MOF Cu (b) is exactly matched with our previous report [34, 35]. Figure 3A (c) shows the XRD pattern of MOF CoCu nanocubes with several peaks at 2θ of about 7.16, 10.2, 12.6, 14.4, 16.3, 17.9, 22.0, 24.5, 26.6, 29.6, 31.2, and 32.3° associated with (011), (022), (112), (022), (013), (222), (114), (233), (134), (044), (244), and (235) diffraction planes of MOF Co [35].…”
Section: Resultssupporting
confidence: 91%
“…As can be seen in Figure 3A, the XRD pattern of MOF Co (a) and MOF Cu (b) is exactly matched with our previous report [34, 35]. Figure 3A (c) shows the XRD pattern of MOF CoCu nanocubes with several peaks at 2θ of about 7.16, 10.2, 12.6, 14.4, 16.3, 17.9, 22.0, 24.5, 26.6, 29.6, 31.2, and 32.3° associated with (011), (022), (112), (022), (013), (222), (114), (233), (134), (044), (244), and (235) diffraction planes of MOF Co [35]. The MOF CoCu nanocubes XRD pattern is identical to that of MOF Co suggesting that the presence of copper has a marginal impact on the crystallinity [36].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, it was found that the peak of SeO x at 58.5 eV has some shift in the Se 3d spectrum (Figure 3c), [26,37,38] approximately a positive shift of 0.66 eV compared with that of the crystalline C 4 S sample, revealing the increase of low‐coordination Se content, which could be attributed to probable existence of Se vacancies in the amorphous C 4 S‐12 h material, which would facilitate the enhanced OER performance [39–40] . Correspondingly, it could be seen that the Se−O−M peak around 530.7 eV [41–42] in the O 1s high‐spectrum (Figure 3d) also has an obvious high‐energy shift. Thus, the electronic structure of this amorphous material could be changed by this mechanical ball milling method.…”
Section: Resultsmentioning
confidence: 97%